Is the Processing of Chinese Verbal Metaphors Simulated or Abstracted? Evidence From an ERP Study - Li, Ying; Lu, Xiaoxiao; Wang, Yizhen; Wang, Hanlin; Wang, Yue (Frontiers in Psychology, 2022)
The theory of embodied semantics holds that verbal metaphors are strongly grounded in sensorimotor experience. Many studies have proven that besides sensorimotor simulation, the comprehension of verbal metaphors also requires semantic abstraction. But the interaction between simulation and abstraction, as well as the time course of metaphorical meaning integration, is not well understood. In the present study, we aimed to investigate whether embodiment or abstraction, or both, is employed in the processing of Chinese verbal metaphor. Participants were asked to read subject-verb metaphorical, verb-object metaphorical, literal-concrete and literal-abstract sentences, and the target words were measured at the verb and the object of each sentence. The results revealed that a similar N400 effect was elicited by the target verbs in the verb-object metaphorical and the literal-concrete sentences, and a similar P600/LPC effect was induced by the target verbs in the subject-verb metaphorical and the literal-abstract sentences, reflecting that the verb-object metaphors trigger a simulation process, while the subject-verb metaphors trigger an abstraction process in the verb processing stage. Moreover, the subject-verb metaphors elicited a stronger P600/LPC effect by the target verbs than the verb-object metaphors, but there was no difference of the P600/LPC caused by the target objects between the two kinds of metaphors, revealing that the metaphorical meaning of a subject-verb metaphor is integrated in the verb processing stage, while that of a verb-object metaphor is reanalyzed in the object processing stage. These results suggest that a verbal metaphor is processed both by simulation and abstraction, and the metaphorical meaning is integrated immediately with the unfolding of the sentence meaning. The position where the semantic conflict lies in a sentence (verb vs. object) modulates the time course of metaphor sentence comprehension.